Young children's sleep patterns and problems in paediatric primary healthcare settings: a multicentre cross-sectional study from a nationally representative sample - BORAN, PERRAN (My University, 2022)
Studies describing paediatric sleep patterns are needed by taking culture into consideration. The aim of this study was to identify parent-reported sleep-wake patterns in young children and explore possible factors influencing sleep problems. The mothers of 2,434 young children enrolled from well-child outpatient clinics in Turkey completed an online survey including sociodemographic variables, Brief Infant Sleep Questionnaire, Edinburgh Postnatal Depression Scale and Generalised Anxiety Disorder scales. Overall, young children in Turkey go to bed late (10:00 p.m.), awaken twice per night for 30 min, and obtain 11.5 h of total sleep, showing no sex-specific differences. Distinct night-time sleep patterns emerged after 18 months of age. Importantly, although currently breastfed healthy children were 3.8-times less likely to sleep through the night, total sleep duration and exclusive breastfeeding duration were higher in children who were not sleeping through the night. Overall, bedsharing was identified in 11.5%, and only room sharing was reported in 52.9%. Parental perception of a child\"s sleep as problematic was 35.8%. Mothers with higher educational attainment were more likely to perceive their children\"s sleep as a problem. Maternal depressive and anxious symptoms and a history of excessive infant crying were the determinants predicting the likelihood of both parent-perceived sleep problems and poor sleepers. The present analysis of sleep structure in infancy and toddlerhood provides reference data for well-child visits. These findings highlight the importance of considering maternal anxiety, depression and behaviour management techniques to cope with fussy infants in addressing childhood behavioural sleep problems.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Nöroloji; Yaşam Bilimleri; Temel Bilimler; Medicine; Health Sciences; Internal Medicine Sciences; Neurology; Life Sciences; Natural Sciences; KLİNİK NÖROLOJİ; Klinik Tıp; Klinik Tıp (MED); SİNİR BİLİMİ; Sinirbilim ve Davranış; Yaşam Bilimleri (LIFE); CLINICAL NEUROLOGY; CLINICAL MEDICINE; Clinical Medicine (MED); NEUROSCIENCES; NEUROSCIENCE & BEHAVIOR; Life Sciences (LIFE); Gelişimsel Sinirbilim; Hücresel ve Moleküler Sinirbilim; Bilişsel Sinirbilim; Genel Sinirbilim; Sinirbilim (çeşitli); Duyusal Sistemler; İnsan Bilgisayar Etkileşimi; Nöroloji (klinik); Fizik Bilimleri; Developmental Neuroscience; Cellular and Molecular Neuroscience; Cognitive Neuroscience; General Neuroscience; Neuroscience (miscellaneous); Sensory Systems; Human-Computer Interaction; Neurology (clinical); Physical Sciences; breastfeeding; child; maternal anxiety; maternal depression; sleep; sleep initiation and maintenance disorders; INFANT SLEEP; MATERNAL ANXIETY; TODDLER SLEEP; 1ST YEAR; TURKISH; QUESTIONNAIRE; RELIABILITY; DEPRESSION; EDUCATION; VALIDITY